A methodological proposal to promote interdisciplinary scientific contents - Saldis, Nancy Edith; Larrosa, Nancy Beatriz; Gómez, Marcelo Martín; Marín, María Andrea; Penci, María Cecilia; López, Abel Gerardo (Universidad Nacional de Córdoba, Faculdad de Ciencias Sociales, Centro de Estudios Avanzados. Maestría en Procesos Educativos Mediados por Tecnología, 2015)
The aim of this paper is to report the experience conducted by a team of professors from the Faculty of Physical and Natural Sciences of the National University of Córdoba. The innovation consists of the inclusion of some material resources and methodologies with ICT in several workshops, seminars and courses for students and teachers from all educational levels: primary, secondary, tertiary and university. Several multiparameter sensors were used and methodologies and elements were adapted in order to facilitate the construction of scientific and technological knowledge; also, a virtual classroom and a blog were created and implemented. A constructivist methodology was chosen and it was based on the resolution of problematic situations through laboratory experiments in order to achieve interdisciplinary content. The experience enabled the exchange of knowledge between students and teachers from different educational institutions and levels, thus enriching experiences and reaffirming habits, expression and communication.